Perfusion‐Derived Dynamic 4D CT Angiography Identifies Carotid Pseudo‐Occlusion in Hyperacute Stroke. Issue 6 (7th July 2016) - Ng, Felix C.; Choi, Philip M.C.; Datta, Mineesh; Gilligan, Amanda
ABSTRACT: BACKGROUND: Differentiation between true acute tandem occlusion involving the extracranial internal carotid artery (ICA) from pseudotandem occlusion with a patent extracranial ICA has important prognostic and therapeutic implications. We explored the utility of perfusion‐derived 4‐dimensional CT angiogram (4D‐CTA) in identifying carotid pseudo‐occlusion in a single‐center pilot study. METHODS: Acute stroke patients with delayed antegrade ICA flow on 4D‐CTA despite an apparent tandem occlusion on conventional single‐phase CTA were prospectively identified over a 2.5‐year period (2013‐2015). RESULTS: Eight patients were identified. Delayed antegrade intracranial flow from the apparently occluded ICA was detected up to 50 seconds after contrast administration on 4D‐CTA. The distal intracranial ICA was the most common site of true occlusion. Reconstruction of the 4D‐CTA images required an additional processing time of 2–3 minutes. CONCLUSIONS: 4D‐CTA is a novel noninvasive technique that can identify carotid pseudo‐occlusion in the acute stroke setting. Our preliminary findings suggest that 4D‐CTA can be easily incorporated into an existing acute stroke neuroimaging protocol.